Large-scale spatial variation and phenotypic integration in three Argynnini species inform about functions and evolutionary drivers of butterfly wings - Polic, Daniela; Yıldırım, Yeşerin; Vila, Roger; Ribeiro Cardoso, Paulo Ricardo; Franzén, Markus; Forsman, Anders (Frontiers in Ecology and Evolution, 2023)
Understanding how large-scale environmental variability may shape the distribution of phenotypic variation remains central to evolutionary biology. Across-species comparisons of trait variation alongside environmental gradients may offer valuable insights into how different species may respond to similar selective pressures. We conducted a comparative morphological study (> 32 degrees latitude and > 47 degrees longitude) on three closely related Argynnini butterfly species, Speyeria aglaja, Fabriciana adippe, and F. niobe. We measured wing size and colouration to assess 1) whether they respond similarly or differently to environmental factors (longitude, latitude, altitude, temperature, precipitation, solar radiation, wind speed); 2) if these factors correspond with those associated with the species’ genetic structure based on a previous study; and 3) whether correlations between phenotypic traits within individuals are species-specific. We found common and species-specific associations of climatic (precipitation, wind speed) and geographic (longitude, altitude) factors with the composite phenotypic variation. Wing size was associated with different variables in the studied species, while melanisation mainly increased in cooler regions in all species, suggesting that the need for temperature regulation is a strong selective pressure on melanisation. Wing size was associated with the genetic structure in all species, highlighting the functional importance of this trait. The environmental drivers associated with the phenotypic variation in S. aglaja and F. adippe were largely the same as those associated with their genetic structure, hinting at a genetic underpinning of the observed morphological variation due to local adaption. We report some distinct intraspecific trait correlations in S. aglaja and F. adippe, indicative of independent phenotypic integration. These phenotypes seem to be associated with protection against predators and thermal regulation in the respective habitats of both species, suggesting that similar selective pressures have resulted in the evolution of different trait combinations. Some of the inter-specific differences could be related to diverging niche breadths and dispersal capacities, exemplifying that the evolution of trait integration and spatial phenotypic differentiation may differ between closely related species with overlapping distribution ranges. Our findings highlight the importance of comparative assessments of variation, and demonstrate that the relative effects of drivers of variability may vary between sister species.